2009
DOI: 10.1111/j.1399-3046.2008.01056.x
|View full text |Cite
|
Sign up to set email alerts
|

Invasive mold infections in iatrogenically immunocompromised children: An eight‐yr review

Abstract: IMI are emerging as an important cause of mortality and morbidity among the growing number of immunocompromised children. A retrospective chart review was performed in all patients with a proven diagnosis of IMI over an eight-yr period (1997-2004) at The Hospital for Sick Children, Toronto, Canada to document the incidence, clinical spectrum, microbiology, treatment, and outcome of pediatric IMI. Twenty-eight patients developed IMI over the study period (10 cancer, 12 HCT, and six SOT patients). IMI occurred i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
(72 reference statements)
2
18
1
2
Order By: Relevance
“…Although data for combination antifungal therapy in children with IMIs are sparse, it is frequently used in practice, as evidenced by our study and by other recent pediatric cohort studies that have reported rates of combination therapy ranging from 32% to 91% [3][4][5]. We found that primary combination therapy was more likely to be used in patients who had received antimold agents before diagnosis.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although data for combination antifungal therapy in children with IMIs are sparse, it is frequently used in practice, as evidenced by our study and by other recent pediatric cohort studies that have reported rates of combination therapy ranging from 32% to 91% [3][4][5]. We found that primary combination therapy was more likely to be used in patients who had received antimold agents before diagnosis.…”
Section: Discussionsupporting
confidence: 60%
“…Compared with previous cohort studies of IA in children, we found more frequent use of extended spectrum triazoles as well as echinocandins, with voriconazole replacing liposomal amphotericin B as the predominant agent for treatment of IA [3][4][5]. This result likely reflects incorporation of evidence primarily in adults showing superiority of voriconazole to amphotericin B deoxycholate in terms of outcome and tolerability [23].…”
Section: Discussioncontrasting
confidence: 36%
“…Treatment efforts for this difficult problem must prevent systemic spread as the evolution of disseminated Aspergillosis is associated with mortality rates as high as 80% [2][3][4]8]. Wide local excision of all involved soft tissue has been discussed as the preferred Joseph A. Molnar, MD, Ph.D., receives research funds from KCI, Inc. (the manufacturer of the VAC®) and receives compensation for presentations at educational symposia sponsored by KCI, Inc. surgical intervention.…”
Section: Introductionmentioning
confidence: 98%
“…Invasive mold infections (IMI) represent a major cause of morbidity and mortality among pediatric patients affected by hematological malignancies and are often associated with poor clinical outcomes despite the use of active antifungal drugs [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%